Touchscreen Inspector in Future Flight Deck Design - Li, Wen-Chin; Wang, Yifan; Korek, Wojciech Tomasz; Braithwaite, Graham (Cranfield University, 2023)
Fifty-one participants were invited to conduct two scenarios which consisted of landing with disturbance (LD) and landing no disturbance (LN) using three inceptors, including sidestick, gamepad and touchscreen on the FSS. Both the system usability scale (SUS) and situation awareness rating technique (SART-10D) were completed by participants at the end of each trial. Therefore, two-way repeated measure ANOVA was applied to analyse participants€™ ratings on SUS for system usability involving two sub-dimensions: usability (SUS-U) and learnability (SUS-L), and SART-10D for situation awareness including three sub-dimensions: demand (SART-D), supply (SART-S) and understanding (SART-U) while interacting with a touchscreen as inceptor for flight control. The inceptors and scenarios are two independent variables, both SUS and SART, and their sub-dimensions were dependent variables.
Keywords: Flight Deck Design'; 'Human-Computer Interaction'; 'Situation Awareness'; 'System Usability'; 'Touchscreen Inceptor'